Environmental concern and its relation to ecological behavior in engineering students from the Private University of Tacna - Bernedo Berríos, Sebastián Martín (2020)
The objective of the research was to determine the relationship between environmental concern and ecological behavior in students of the Faculty of Engineering of the Private University of Tacna, through a descriptive study of correlal level, the survey technique was used using the questionnaire as an instrument. the sample of 310 randomly and proportionally selected students came from the six professional schools that make up the faculty, among the most outstanding results; it was found that 53.9% of students consider their level of concern about environmental issues to be regular, the most prominent dimension being the "Control Locus", where students consider their level of taking on the role of the energy and environmental crisis to be high, as well as when comparing by professional schools; Environmental Engineering students had higher average values; 53.2% of students said that their level of ecological behavior, which seeks to prioritize environmental care is regular, the most appreciable dimension was "Energy Conservation", again highlighting the students of the School of Environmental Engineering who presented the highest values in terms of average. It is concluded that there is a direct and significant relationship (Spearman's Rho s 0.614 and p x 0.000) between environmental concern and ecological behavior in students.